A noção eclesiológica de comunhão na obra de Jean Jérôme Hamer, O.P. - Ferreira, Antonio Luiz Catelan (Revista Eclesiástica Brasileira, 2012)
A comemoração dos 50 anos do início do Concílio Vaticano II oferece ocasião para a retomada de suas ideias mestras e dos personagens que marcaram sua história. Os elementos mais destacados da eclesiologia conciliar têm sido já amplamente estudados, como também os teólogos que mais influência sobre ele exerceram. Um dos peritos conciliares, o Card. Jean Jérôme Hamer, O.P., autor de uma influente obra eclesiológica, L’Eglise est une communion, publicada no mês que antecedeu imediatamente à abertura do Concílio, não tem sido estudado e sua contribuição para a eclesiologia do Concílio não tem recebido a atenção que sua importância merece. Este estudo apresenta a peculiar proposta da noção de comunhão deste autor, em suas linhas gerais, como também sua articulação original com a noção de povo de Deus e as consequências que o autor extrai daí para a compreensão de importantes questões, como a da relação entre Igreja local e Igreja universal, entre a colegialidade e o primado. Abstract: The celebration of the 50 years of the beginning of the Second Vatican Council gives us an occasion for the resumption of their key ideas and of the contribution of the theologians that have marked its history. Indeed, the most prominent elements of the ecclesiological contributions of this Council have already been widely studied, as well as theologians who exercised more influence over him. This paper studies the peculiar notion of communion proposal made by J. Hamer, O.P., Belgian, expert of the Pontifical Council for Promoting Christian Unity during the four sessions of the council. He is the author of an influential work ecclesiological, L´Église est une communion, published in September 1962, the month immediately preceding the opening of the Council. But this author has not yet been systematically studied and their contribution to ecclesiology has not received the attention its importance deserves. The present study highlights the original articulation between the both notions, communion and People of God and the consequences that the author draws from there to the understanding of important issues like the relationship between the local Church and the universal Church, between collegiality and primacy.